Estimation of protein digestibility in bran from different rice varieties. - Andreevska, Danica; Andov, Dobre; Gjorgovska, Natasha; Levkov, Vesna; Menkovska, Mirjana; Grigorova, Svetlana; Dimitrovski, Trajche (University Ss Ciril and Methodius in Skopje, Institute of Animal Science, 2018)
Rice is an important cereal crop in the Republic of Macedonia. The process of the post-production of paddy rice results in certain categories of products: brown rice (or cargo), white rice, broken rice, rice hull and rice bran as by-products, which have a wide variety of applications. The focus of our study was to estimate the protein digestibility in rice bran of 8 rice varieties (Prima riska – as standard, San Andrea, Onice, Gloria, Roma, Gala, Halilbey and Gönen). The protein digestibility was determined using in vitro method with pepsin dissolved in HCl. There was a statistically significant difference between the rice varieties in the digestibility of protein and in total fat. The protein digestibility of rice bran ranged from 81.79% in the Turkish variety Gönen to 88.58% in the Italian variety Gloria. These results suggest that rice bran is a good source of protein with good biological value and digestibility
Keywords: rice bran; protein; digestibility